Reducing Transportation Costs in Distribution Networks - LI, Xi (Institutional Knowledge at Singapore Management University, 2006)
In this work, we model the conflicting objectives in a distribution network, i.e. trade-offs between transportation costs, inventory and time scheduling requirements. Transportation costs include time costs, truck setup costs, and the number of trucks used. The model is formulated as an integer program and a solution of two-stage metaheuristic is provided. Computational experiments are conducted to test the algorithms.